2013
DOI: 10.1371/journal.pone.0073345
|View full text |Cite
|
Sign up to set email alerts
|

Application of Concave Microwells to Pancreatic Tumor Spheroids Enabling Anticancer Drug Evaluation in a Clinically Relevant Drug Resistance Model

Abstract: Intrinsic drug resistance of pancreatic ductal adenocarcinoma (PDAC) warrants studies using models that are more clinically relevant for identifying novel resistance mechanisms as well as for drug development. Tumor spheroids (TS) mimic in vivo tumor conditions associated with multicellular resistance and represent a promising model for efficient drug screening, however, pancreatic cancer cells often fail to form spheroids using conventional methods such as liquid overlay. This study describes the induction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 41 publications
1
69
1
1
Order By: Relevance
“…It was previously reported that PDAC cells are difficult to cohere into spheroids capable of being used for high-throughput drug assays. 45 Data in Figure 2C and D show that the spheroids formed using the proposed method are highly reproducible. Light microscopy shows that these spheroids are uniform in shape, have smooth/defined boundaries, and are dense enough to be used for various assays (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…It was previously reported that PDAC cells are difficult to cohere into spheroids capable of being used for high-throughput drug assays. 45 Data in Figure 2C and D show that the spheroids formed using the proposed method are highly reproducible. Light microscopy shows that these spheroids are uniform in shape, have smooth/defined boundaries, and are dense enough to be used for various assays (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…We based this study on pancreatic adenocarcinoma cell lines (PDAC), since, in ours and others experience, PDAC cells are difficult to culture into cohesive and manageable spheres when any of the traditional spheroid forming methods are used. 45 The proposed technique enables simultaneous, cost-and time-effective generation of numerous spheroids. The tumor spheroids are extremely uniform in nature and do not easily dissemble when handled, allowing increased reproducibility and scalability.…”
Section: Introductionmentioning
confidence: 99%
“…Microfabricated well arrays (Fig. 2a) were developed to increase the production of homogeneous tumor spheroids by using the geometrical confinement to trap similar numbers of cells in each well[3034]. Other research groups have developed micro-chambers or micro-posts in microfluidic channels to trap clusters of cells to control spheroid size and simplify liquid handling procedures[35].…”
Section: Simple But Informative Single Channel Microscale 3d In VImentioning
confidence: 99%
“…Data obtained using these in vitro models may explain the involvement of interaction between cancer cells and the extracellular matrix (ECM) or between cancer cells and stromal cells in the induction of EMT. In contrast to these conventional 2-dimensional cell culture systems, 3-dimensional (3D) tumor spheroids (TSs) may be a more reliable model reflecting the characteristics of in vivo tumors more closely [12][13][14]. To incorporate tumor microenvironmental factors into TSs representing the architecture of in vivo tumors, a directmixed co-culture of TSs with fibroblasts using the hanging-drop method has been reported [15].…”
Section: Introductionmentioning
confidence: 99%